2019
DOI: 10.1002/stem.3098
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of formin mDia2 alters lamin B1 levels and increases osteogenesis in stem cells

Abstract: Nuclear actin plays a critical role in mediating mesenchymal stem cell (MSC) fate commitment. In marrow-derived MSCs, the principal diaphanous-related formin Diaph3 (mDia2) is present in the nucleus and regulates intranuclear actin polymerization, whereas Diaph1 (mDia1) is localized to the cytoplasm and controls cytoplasmic actin polymerization. We here show that mDia2 can be used as a tool to query actinlamin nucleoskeletal structure. Silencing mDia2 affected the nucleoskeletal lamin scaffold, altering nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…We showed that during the cell division of CFU-Es, the localization of mDia2 changed from the nucleus to the cytoplasmic membrane. This result is in agreement with previous findings obtained using human and mouse cells 29 , 30 . Moreover, we found that the localization of mDia2 remained unchanged in the nucleus during the enucleation of erythroblasts.…”
Section: Discussionsupporting
confidence: 94%
“…We showed that during the cell division of CFU-Es, the localization of mDia2 changed from the nucleus to the cytoplasmic membrane. This result is in agreement with previous findings obtained using human and mouse cells 29 , 30 . Moreover, we found that the localization of mDia2 remained unchanged in the nucleus during the enucleation of erythroblasts.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, knocking down mDia2 leads to a decrease in osteogenesis, while silencing of mDia2 has no effect on osteogenesis [57]. Knocking down mDia2 also leads to a decrease in the expression and structure of lamin-B1 [58]. However, it is not clear whether mDia2 knockdown decreases osteogenesis directly through nuclear actin or indirectly through lamin-B1.…”
Section: Actin Cytoskeleton and Rho Pathwaymentioning
confidence: 98%
“…In addition to being found at the periphery, lamin A/C and lamin-B1 interact with chromatin in the nucleoplasm [60,61]. This suggests that mDia2-mediated actin polymerization affects lamin integrity and composition, which might be crucial for MSC differentiation [58].…”
Section: Actin Cytoskeleton and Rho Pathwaymentioning
confidence: 99%
“…48h after siRNA treatment, cell nuclei were isolated, plated onto 0.1% Poly-L-Lysine coated plates for adherence and subjected to AFM testing to obtain force-displacement curves as we reported previously ( Fig. 1a ) 19 . As shown in immunolabeled nuclei images ( Fig.…”
Section: Data Collection Modeling Simulation Setup and Methodsmentioning
confidence: 99%